Growth and functional characteristics of male athletes 11-15 years of age - Malina, R. M.; Rozek, K.; Ignasiak, Z.; Slawinska, T.; Fugiel, J.; Kochan, K.; Domaradzki, J. (Human Movement, 2011)
To evaluate the growth and functional characteristics of male athletes 11-15 years of age. Basic procedures. The sample included 190 boys, 10.5-15.4 years, undergoing training of sport schools for track and field (136) and other sports (54). Height, weight, three skinfolds and % Fat (NIR) were measured. Grip strength, standing long jump, 2 kg medicine ball throw and 20 m sprint were tested. Track and field athletes were compared by discipline and to athletes in other sports using MANCOVA (multivariate analysis of covariance). Multiple linear regression analysis was used to estimate the relative contributions of age, body size and adiposity to the four functional indicators in two age groups, those 11-13 years and 14-15 years. Main findings. All variables except the standing long jump and 20 m sprint differed significantly by track and field discipline. Only height and ball throw differed among athletes in other sports. Track and field athletes had a significantly lower BMI and % Fat and performed better in the jump and sprint than athletes in other sports. Variance explained in each of the functional indicators was greater in younger than in older athletes. The sum of skinfolds and % Fat exerted a negative influence on all functional indicators. Conclusions. Trends in body size of male athletes attending sport schools were consistent with observations for youth male athletes in several sports. Height, weight and adiposity accounted for significant portions of variation in the four functional indicators in each age group, but the explained variance was higher in younger athletes.